Transformasi Inovasi Pembelajaran Digital Guru IPS Dalam Implementasi Kurikulum Merdeka Pada Era Perubahan Digital - Nur Indah Miftahul Jannah; Moh. Sutomo; Salsabila Dwi Nur Rohma (Journal Education Innovation (JEI), 2026)
The quick progress of online education has changed how teaching is done, making the examination of new digital learning methods crucial. Although numerous studies have explored technology use in educational settings, there is a lack of research concerning how Social Studies educators modify and create new approaches within the Merdeka Curriculum, indicating a considerable gap in the existing literature. This research seeks to determine the types of digital innovations utilized by Social Studies educators and examine the factors that promote or hinder their implementation in junior high schools. Employing a qualitative case study method at SMPN 1 Jember, data were gathered through interviews, classroom observations, and document examination, and subsequently analyzed thematically to uncover significant patterns and insights. The results show that teachers use digital methods like interactive presentations, online tests, and collaborative tools to improve student involvement and learning results. These practices signify a new adjustment to the Merdeka Curriculum. The research emphasizes the significance of creative teaching and support from institutions, providing direction for professional growth and the development of curricula.